Strategic Management of Cost of Production Operations In the 0il Fields: بحث تطبيقي في شركة نفط الوسط (شركة عامة) (Journal of Accounting and Financial Studies ( JAFS ), 2019)
The use of the entrance diffraction hexagon continuous improvement of operations in order to achieve the rationalization of activities, costs and efficiency in the use of available resources and reduce the incidence of damage and waste and recycling, as the accounting information system does not meet the surface production processes oil fields cost management requirements in the measurement and evaluation of the costs of each activity and development of indicators to evaluate the efficiency and effectiveness of production processes and to cover the shortcomings of currently approved by the company so cost accounting system has Find addressed the use of strategic cost management techniques, including the entrance diffraction hexagon for continuous improvement, and ensure the theoretical side of research methodology and the concept of cost strategy and technology management either practical side dealt with the costs of managing the application of the entrance to the hexagon diffraction for continuous improvement oil field east of Baghdad and the center which is run by oil company one of the formations and the Federal Ministry of Oil and the search is over a set conclusions and recommendations